Day 1 Tue, February 04, 2020 2020
DOI: 10.2118/199716-ms
|View full text |Cite
|
Sign up to set email alerts
|

Case History of Drainage Mapping and Effective Fracture Length in the Bakken

Abstract: Understanding effective fracture length and characterizing drainage patterns is critical for optimal development of unconventional resources. This paper documents a comprehensive field experiment in the Bakken formation, where several fracture diagnostic technologies and drainage mapping methods were used in a unique project setup to measure effective fracture length and map drainage. Two vertical wells (V1 and V2) were drilled 1,000 ft away from a Bakken lateral (H1) with 10 years of production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In contrast, the DFITs represent local measurements that the heterogeneity of the formation can cause. Another difference between this work and the work of Cipolla et al [16] and Fowler et al [9] is that the contribution of the Three Forks is considered in the modeling. The numerical modeling section will discuss more details about the modeling process.…”
Section: Problem Statementmentioning
confidence: 87%
See 3 more Smart Citations
“…In contrast, the DFITs represent local measurements that the heterogeneity of the formation can cause. Another difference between this work and the work of Cipolla et al [16] and Fowler et al [9] is that the contribution of the Three Forks is considered in the modeling. The numerical modeling section will discuss more details about the modeling process.…”
Section: Problem Statementmentioning
confidence: 87%
“…Rezaei et al [15] simulated stress changes due to depletion and their effect on fracture propagation and reorientation from offset wells under different stress contrasts. Cipolla et al [16] and Fowler et al [9] modeled stress changes in a field-scale laboratory study. Morsy et al [17] reported a numerical simulation workflow to optimize offset well design through sensitivity analysis in the Wolfcamp formation.…”
Section: Bakkenmentioning
confidence: 99%
See 2 more Smart Citations
“…Where the length represents the extent of the fracture in the reservoir and the drainage area, fracture height is the vertical coverage of the HF treatment. For an appropriate design of HF jobs, fracture height estimation is essential for optimum well placement and geometry estimation [8,9].…”
Section: Introductionmentioning
confidence: 99%